Factors Associated with Malnutrition and Its Impact on Postoperative Outcomes in Older Patients - Venianaki, Maria (J Clin Med, 2021)
Malnutrition is associated with dismal treatment outcomes in older patients but its impact in geriatric surgery has not been studied extensively. Herein, we report the prevalence of malnutrition risk, its risk factors and its association with postoperative outcomes in older patients undergoing operations of general surgery. This is a retrospective analysis of a prospectively maintained database including patients older than 65 years who were to undergo general surgery operations between 2012 and 2017. The Malnutrition Universal Screening Tool (MUST) was used for nutritional risk. Demographics, socioeconomic data, site and magnitude of the operation, various measures of comorbidity and functional dependence as well as postoperative complications based on Clavien–Dindo classification and length of stay were recorded. There were 501 patients. A total of 28.6% of them were at intermediate malnutrition risk (MUST = 1) and 14.6% were at high malnutrition risk (MUST ≥ 2). Variables independently associated with malnutrition risk (MUST ≥ 1) were smoking (Odds Ratio, OR:1.6, p = 0.041), upper gastrointestinal (GI) tract surgery (OR:20.4, p < 0.001), hepatobiliary-pancreatic surgery (OR:3.7, p = 0.001), lower GI surgery (OR:5.2, p < 0.001) and American Society of Anesthesiologists (ASA) class III/IV (OR:2.8, p = 0.001). In the multiple regression analysis adjusted for several confounding variables, the MUST score was significantly associated with postoperative death (OR:9.1, p = 0.047 for MUST = 1 and OR:11.9, p = 0.035 for MUST score ≥ 2) and postoperative hospital stay (adjusted incidence rate ratio, 1.3, p = 0.041 for MUST = 1 and 1.7, p < 0.001 for MUST ≥ 2). Malnutrition risk was highly prevalent in this sample, particularly in patients with operations of the gastrointestinal tract, in patients with poor physical status and it was associated with postoperative mortality and length of stay.